Development and validation of the newly developed Preschool Theory of Mind Assessment (ToMA-P) - Fu, I-Ning; Chen, Cheng-Te; Chen, Kuan-Lin; Liu, Meng-Ru; Hsieh, Ching-Lin (Frontiers in Psychology, 2024)
Introduction Theory of mind (ToM) refers to the ability to understand and attribute mental states to oneself and others. A ToM measure is warranted for preschool children to assess their ToM development from a multidimensional perspective (i.e., cognitive and affective dimensions). This study aimed to develop the Preschool Theory of Mind Assessment (ToMA-P) and to evaluate its construct validity and applicability. Methods The ToMA-P was developed based on comprehensive literature review and revised with expert panel feedback. Its psychometric properties were evaluated in 205 typically developing preschoolers with Rasch analysis for its dimensionality, item difficulties, and convergent validity. Results The results indicated that all ToMA-P items, except for one, fit the hypothesized two-dimensional construct. The item difficulties in the cognitive and affective dimensions followed developmental sequences. The ToMA-P scores exhibited good convergent validity, as evidenced by its significant correlations with age, verbal comprehension, adaptive functions, and daily ToM performance (p < 0.05). Children’s responses and behaviors also showed that the ToMA-P has good applicability. Discussion This study provides empirical evidence that the ToMA-P measures cognitive and affective ToM following developmental sequences, and that it has potential as a clinical tool for assessing ToM in preschool children.